Pandemic Communication: Information Seeking, Evaluation, and Self-Protective Behaviors in Vietnam and the Republic of Korea - Diers-Lawson, Audra; Johnson, Sophie; Clayton, Teela; Kimoto, Riko; Tran, Bach Xuan; Nguyen, Long Hoang; Park, Kisoo (Frontiers in Communication, 2021)
Saliou (1994) argued that pandemics are special kinds of crises and requires the public health sector to focus on: (1) reducing uncertainty, (2) rumor mitigation, and (3) ensuring the public reduces their risk of contracting the disease. With this as a backdrop, the central aim of this research is to better understand the connections between public information seeking, evaluation, and self-protective behaviors in the COVID-19 pandemic and focuses on a comparison between the Republic of Korea and Vietnam to provide insights into the influence of the individual, institutional, and information factors influencing people’s experience with COVID-19. Thus, there are two major contributions of this study. First, it provides a cross-theory evaluation of the factors that contribute to information seeking, evaluation, and self-protective behaviors. Second, the study identifies potentially critical differences in information seeking, evaluation, and self-protective behaviors based on acute disease reproduction in countries with a successful pandemic suppression history. Findings suggest that in countries where there are high levels of trust and satisfaction even small changes in the infection rates lead to different information seeking and self-protective behaviors.